Therapeutic Effect of CAOLD Chemotherapy Regimen on Patients With Relapsed/Refractory Angioimmunoblastic T-Cell Lymphoma: A Case Study - Liu, Yu; Li, Pingping; Qian, Liren (Frontiers in Oncology, 2022)
Angioimmunoblastic T-cell lymphoma (AITL) is a kind of peripheral T-cell lymphomas (PTCL) with the feature of highly invasive. At present, patients are often treated with CHOP or CHOP-like regimens which is of poor prognosis whilst having high recurrence rate. Once the patient fails to achieve remission or relapse after the first-line treatment, many salvage chemotherapy regimens are always ineffective, and the long-term survival will be difficult to achieve for them. In this circumstance, more effective therapy methods are needed. In this study, two patients with relapsed/refractory AITL were treated with CAOLD regimen (cyclophosphamide 400mg/m2 qd d1; cytarabine 30mg/m2 qd d1-d4; vindesine 2mg/m2 qd d1; pegaspargase(PEG-ASP) 2500iu/m2 qd d2; dexamethasone 7.5mg/m2 qd d1-d5) and the report of long-term remission were received after chemotherapy. One is still alive after received complete remission (CR) after two cycles of chemotherapy, who has been following up for eighty-two months. Besides, another patient received partial remission (PR) after the first course of chemotherapy. Then CR was obtained after four courses of consolidation chemotherapy. The patient has been following up for sixty-three months and is still alive. Both of them achieved long-time survival. These two successful cases demonstrated that CAOLD regimen can be a better choice for relapsed/refractory AILT and offers hope of breakthrough in this medical field.